Increasing fruit set of european pears in Southern Brazil - Brighenti A.F.* (2012)
Poor yield is one of the biggest problems with the production of pears in Brazil. The absence of fertilization in flowers of pear, results in a lower fruit set and thus reduces the productivity of the orchard. When pollination is insufficient, it is necessary to use bioregulators to improve this situation. The objective of the present study was to evaluate the effects of different products in increasing fruit set and productivity of 'Williams', 'Red Bartlett' and 'Packham's Triumph' (Pyrus communis L.) pears. The experiment was conducted in São Joaquim city (28°17' S, 49°56' W, altitude 1350 m), Santa Catarina State, Brazil. The experimental design was conducted in a randomized block design. The rate of fruit set was determined two months after the application of the products. The treatments were: 1) Promalin® (1 ml L -1) at full bloom; 2) Promalin® (0.3 ml L-1) applied at the beginning, full and end of the bloom; 3) Prohexadione-Ca (0.65 g L -1) at full bloom; 4) Prohexadione-Ca (1.25 g L-1) at full bloom; 5) Prohexadione-Ca (2.5 g L-1); 6) ReTain® (2 g L -1) 15 days after the full bloom; 7) Promalin® (1 ml L -1) at full bloom + ReTain® (2 g L-1) 15 days after the full bloom; 8) Promalin® (1 ml L-1) + ReTain® (2 g L -1) at full bloom; 9) Promalin® (1 ml L-1) + Prohexadione-Ca (0.65 g L-1) at full bloom; and 10) Control (water). The use of growth regulators is necessary to increase the fruit set, productivity and, therefore, profitability of European pears in the environmental conditions of southern Brazil. The application of Promalin® (1 ml L-1) at full bloom + ReTain® (2 g L-1) 15 days after the full bloom, was the most successful for 'Packham's Triumph' and 'Williams'. The application of Prohexadione-Ca (2.5 g L-1) at full bloom, was the most appropriate for 'Red Bartlett'.